Isolation of fungi using the diffusion chamber device FIND technology - Libor, Benjamin; Harms, Henrik; Kehraus, Stefan; Egereva, Ekaterina; Crüsemann, Max; König, Gabriele M. (Beilstein Journal of Organic Chemistry, 2019)
Fungi are an important source of bioactive metabolites. The Fungal one-step IsolatioN Device (FIND) technology allows the isolation of rare fungi from terrestrial and marine samples. The FIND comprises a multi-chambered micro agar plate, where initially only one fungal part (e.g., hyphal cell, mycelial fragment or spore) is located in each chamber. After inoculation the device is placed back into the original natural environment of sample collection, to ensure favourable growth conditions. Experiments were carried out with terrestrial soil and marine sediment, as well as sea water samples to validate this method. This yielded axenic cultures of 12 different filamentous fungi, one of them being the marine-adapted fungal strain Heydenia cf. alpina. The latter produced two new terpenoids, which are the first secondary metabolites from this genus.
Keywords: FIND; fungal one-step isolation device; Heydenia cf. alpina; natural products; terpenes